Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1360
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task Identification of Entities, Relations, and Coreference for Scientific Knowledge Graph Construction

Abstract: We introduce a multi-task setup of identifying and classifying entities, relations, and coreference clusters in scientific articles. We create SCIERC, a dataset that includes annotations for all three tasks and develop a unified framework called Scientific Information Extractor (SCIIE) for with shared span representations. The multi-task setup reduces cascading errors between tasks and leverages cross-sentence relations through coreference links. Experiments show that our multi-task model outperforms previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
417
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 478 publications
(484 citation statements)
references
References 32 publications
2
417
0
6
Order By: Relevance
“…5 annotated abstracts per domain serving as training data are sufficient to build a performant model. Our active learning results for SciERC [28] and ScienceIE17 [2] datasets were similar. The promising results suggest that we do not need a large annotated dataset for scientific information extraction.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…5 annotated abstracts per domain serving as training data are sufficient to build a performant model. Our active learning results for SciERC [28] and ScienceIE17 [2] datasets were similar. The promising results suggest that we do not need a large annotated dataset for scientific information extraction.…”
Section: Discussionsupporting
confidence: 55%
“…It can be observed that Agr, Med, Bio, and Ast classifiers are the best in extracting PROCESS, METHOD, MATERIAL, and DATA, respectively. For SciERC [28] and ScienceIE17 [2] similar results are demonstrating that MNLP can significantly reduce the amount of labelled data.…”
Section: Traditionally Trained Classifiersmentioning
confidence: 64%
See 1 more Smart Citation
“…We refer to this split as ACE05-E in what follows. The SciERC corpus (Luan et al, 2018) provides entity, coreference and relation annotations from 500 AI paper abstracts. The GENIA corpus (Kim et al, 2003) provides entity tags and coreferences for 1999 abstracts from the biomedical research literature with a substantial portion of entities (24%) overlapping some other entity.…”
Section: Methodsmentioning
confidence: 99%
“…KGs have been used to improve NLP performance in a wide variety of genres, including summarization or information extraction from EHRs and answering medical questions (17,28,29,33,42,62,63). KG-derived embeddings used alone, or in combination with text-derived features (48) improved performance of a variety of NLP tasks, including named-entity recognition (64), coreference resolution (65) and relation extraction (66).…”
Section: Natural Language Processing Applicationsmentioning
confidence: 99%